Criterias for the selection of rabbits suitable for animal-assisted work with the visually impaired : Preliminary study - Iváncsik, Réka; Molnár, Marcell (Acta Agraria Kaposváriensis, 2021)
Animal assisted interventions in everyday life can help reduce stress and make life of the visually impaired more complete. For this, not only dogs are available, but also other animal species. We chose the dwarf rabbit for this purpose. The dwarf rabbit is a popular pet, soft, confidential, hands-on; can be taught basic rules, and its care needs are easier to meet for a visually impaired than a dog’s. The objective of our research was to develop and test a set of criteria for the selection of rabbits suitable for the visually impaired, furthermore, to determine whether a person with sight is able to select rabbits for the visually impaired, or whether there are large differences in their assessment? In the course of research, we developed a 14-point criteria that included confidential questions, pleasant experience questions and questions about the stress of rabbits. The scoring scale ranged from 1 to 5, with the highest point marking the most suitable rabbit. The rabbits in the study were of 6 to 12 months of age, tamed for four generations, of different sizes, hair lengths and colours. The study included 12 special education undergraduate students and one person with visual impairment. The participants worked in pairs, first blindfolded and then with sight of the rabbits. The rabbits were assigned in random order, so students didn’t know what number of point the rabbits had previously received. The eye-binding of the students did not affect the scoring, but the visually impaired subject gave the rabbits an average of 0.1 points higher. Because the scores for each student were high, we did not get a significant result. We looked at who at what chance could have given each points. It turned out that the visually impaired gave 5 points - 10% of the time more often - and gave 3 points - 3% - than the undergrad students. We looked at which of the 14 aspects had greater differences in their perception: there were differences, but they were not significant. Comparing the rabbits, we received a significant difference, based on which this criteria system may be useable for the selection of rabbits suitable for visually impaired, as significant differences were discovered between rabbits. People with sight can also use the test, but they slightly more rigorously. It is recommended to conduct further studies involving several visually impaired people.